Análisis de la actividad económica agropecuaria y la vulnerabilidad socioeconómica de los hogares de la Parroquia El Tambo, Cantón Catamayo, año 2013 - Pullaguari Ovelencio, Natalia del Rocío (2016)
The inhabitants of the parish El Tambo, to carry out production, take rudimentary production processes from their ancestors, implying low income for these farmers, who keep these poor agricultural practices. Besides these farmers conduct a market analysis, often wrong, that determines the success or failure of production. That is why this research entitled "Analysis of agricultural economic activity and socio-economic vulnerability of households in the parish El Tambo Region Catamayo , during 2013 " arises ; which has the general objective to analyze the current situation of this activity and the vulnerability of people in the above parish. To carry out this study survey was applied to 288 households, the information collected is used it to form a database and estimate a production function where its independent variables are, use of improved seeds, use of financing and value of wage labor for this method Feasible Generalized Least Squares (FGLS) is used, with the help of Statistical Software Spss 17 and Stata 11. Using statistical methods, the percentages of the variables involved in the regression and indicators of socioeconomic vulnerability, previously proposed in the project was calculated was obtained. The main result of the research was that the parish is purely agricultural Tambo, since 75.7 % of heads of households are engaged in this activity, where the predominant products in this sector are maize, cucumber , tomato , kidney beans and peppers. But it must be stressed that this activity does not pay enough income, since 66.35 % of people living in poverty of which 30.75 % of them are immersed in extreme poverty.